Fundamental Characteristics of New Juvenile Criminal Justice System of the Republic of Serbia - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2026)
By adopting its new Law on Juvenile Perpetrators of Criminal Offences and Criminal – Legal Protection of Minors in 2005, the Republic of Serbia joined a small number of contemporary states that regulate the criminal – legal status of juveniles in a special manner. In that way, the legal position (rights, obligations and responsibilities) of juveniles as both perpetrators as well as victims of criminal offences was arranged as a whole in a separate legal text. This new juvenile criminal justice system is based upon numerous international and European standards, which have been implemented in the legal system that has been coming to life in the past couple of years of their application. New legal provisions regulate substantial, procedural and executive criminal law, so that it could fully accomplish its proclaimed goal – education, re-education and proper development of juveniles. In this paper, the author draws attention to the term, subject, sources, principles and fundamental characteristics of juvenile criminal law, from the standpoints of legal theory, judicial practice and legal literature.